Pengaruh Work Engagement, Job Satisfaction dan Job Insecurity terhadap Turnover Intention melalui Komitmen Organisasi sebagai Variabel Intervening - Yulies Ayu Lestari; Ari Kristiana; Slamet Bambang Riono; Hendri Sucipto; Nur Aisyah (Lembaga Pengembangan Kinerja Dosen, 2026)
The high level of turnover intention in the retail industry is a critical issue, as it may disrupt operational stability and reduce company productivity. A high turnover intention reflects employees’ tendency to leave the organization, which can generate additional costs for recruitment, training, and adaptation, while also creating operational instability. This study aims to examine the influence of work engagement, job satisfaction, and job insecurity on turnover intention, with organizational commitment as an intervening variable, among employees of Toserba Yogya Losari. The research employed a quantitative method with a total sampling technique, involving all 56 employees as respondents. Data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The results reveal that job satisfaction and job insecurity significantly affect organizational commitment, with T-statistics of 2.338 and 4.448 and p-values of 0.019 and 0.000, respectively. Conversely, work engagement has no significant effect on organizational commitment, as shown by a T-statistic of 0.070 and a p-value of 0.944. Furthermore, work engagement, job satisfaction, and job insecurity were not found to have significant effects on turnover intention. Organizational commitment, acting as an intervening variable, was also shown to have no significant influence on turnover intention, with a T-statistic of 1.035 and a p-value of 0.301. These findings highlight the role of job satisfaction and job insecurity in shaping organizational commitment, although they do not directly reduce employees’ turnover intention.